A Method to Determine Gravity Wave Net Momentum Flux, Propagation Direction, and "Real" Wavelengths: A GPS Radio Occultations Soundings Case Study. Issue 6 (15th June 2018) - Alexander, P.; Schmidt, T.; de la Torre, A.
Abstract : Atmospheric gravity waves (GW) serve as an essential mechanism in the transport of energy and momentum flux from the low to the upper atmosphere. In the last decades satellite observations have become an important part in the analysis of GW due to their global and frequent coverage. Present procedures often provide GW absolute momentum flux (MF), ambiguous 3‐D propagation direction, and apparent vertical wavelengths. We here introduce a method with close sounding quartets, which allows the calculation for GW of the net MF, the definite propagation direction, and "real" wavelengths. Among the satellite observational techniques, Global Positioning System (GPS) radio occultation (RO) retrievals provide temperature profiles that after adequate processing may yield GW properties like wavelengths, MF, and energy. Our procedure is illustrated by an example under requirements that tend to ensure that four GPS RO soundings are observing the same GW. The future increase of satellite measuring devices due to new missions (including GPS RO) will lead to a higher spatial and temporal density of profiles that may eventually allow the attainment of GW climatologies of net MF, propagation direction, and "real" vertical wavelengths. Key Points: Previous GW parameters solution schemes are modified for the use of close sounding quartets The method calculates GW propagation direction, net MF, and "real" (not apparent) vertical wavelength The future increase of soundings may lead to GW climatologies of the above parameters by this method